PEMBELAJARAN BERBASIS PROYEK: MENGEMBANGKAN KREATIVITAS DAN KEMAMPUAN KOLABORATIF - Siminto Siminto; Muhamad Majdi; Alim Hardiansyah; Agus Rofi'i; Achmad Gazali (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Currently, the world is undergoing a shift to the age of society 5.0, where all aspects of human life depend on information technology. The paradigm of education has changed in the era of society 5,0, which is centered on the creation of knowledge and the innovative use of knowledge. Students are required to have critical thinking skills, communication, collaboration, creativity, adaptive skills, and technological skills. Therefore, to address the technological challenges of learning models also undergo increases. One of them with project-based learning is a learning model that prioritizes students as subjects or centres of learning. Students are called student centers and teachers are called facilitators. In this learning, the ultimate goal to be achieved is to be able to produce a real product. The aim of this research is to identify concepts and analyze the impact of Project Based Learning (PBP) on the development of creativity and collaborative skills. This research is expected to be motivating in learning. This research is qualitative descriptive research using the methodology of literary study. Research results show that student creativity is significantly influenced by project- based learning. Project-based learning teaches students to think luwes, think creative, innovate, collaborative, evaluative, and communication skills.